Membaca Ulang Konsep Otonomi Daerah Sebagai Fragmen Dari Konsep Daerah Swatantra Masa Kerajaan Nusantara - Syukron, Benny Musta'an (DAS Institute, 2025)
The concept of Otonomi Daerah is considered a novelty in post-reform government. However, the concept of Otonomi Daerah has actually been around since the days of the Nusantara Kingdom, known as the Daerah Swatantra. This study aims to compare Otonomi Daerah in the modern era with the Daerah Swatantra during the Nusantara Kingdom. This research was conducted using the Heuristic method by collecting various historical literature on the concepts of Otonomi Daerah and Daerah Swatantra to review the differences and similarities between the two concepts, then a comparison was made and a synthesis was drawn from the two concepts. It can be said that the concept of regional autonomy in modern Indonesia has significant differences with the autonomous regions in the era of the Nusantara Kingdom in particular, but there are still similarities between the two concepts. The concept of regional autonomy used in the Modern Indonesian Government is an attempt to take a residual part of the past by first modifying it to suit the interests of the times